2001
DOI: 10.1139/v00-177
|View full text |Cite
|
Sign up to set email alerts
|

Excess electrons in aqueous glasses and crystalline ice

Abstract: Experimental studies of excess electrons in aqueous glasses and crystalline ice are reviewed. Emphasis is placed on studies of the two main optical absorption bands, the well known visible band, which is similar to that of the solvated electron in water, and the IR band which has λmax [Formula: see text] 2950 nm. Under some circumstances partial conversion of the IR-absorbing species to the visible-absorbing species has been observed. Evidence indicates that the two species are due to electrons trapped in dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…Pulsed radiolysis experiments of pure water ices revealed that the optical absorption due to free electrons in water ice decay on the timescale of a few nanoseconds to a few microseconds. The lower the temperature, the longer the lifetime of the free electrons in this range (Gillis & Quickenden 2001). Thus, under our experimental conditions of long-term UV photolysis followed by slow spectral scanning we would expect that there would be no free electrons present in these ices at 20 K. Electrons would have more than ample time to become attached to H 2 O or OH within the ice, forming trapped H 2 O À or OH À negative ions (anions).…”
Section: Discussionmentioning
confidence: 95%
“…Pulsed radiolysis experiments of pure water ices revealed that the optical absorption due to free electrons in water ice decay on the timescale of a few nanoseconds to a few microseconds. The lower the temperature, the longer the lifetime of the free electrons in this range (Gillis & Quickenden 2001). Thus, under our experimental conditions of long-term UV photolysis followed by slow spectral scanning we would expect that there would be no free electrons present in these ices at 20 K. Electrons would have more than ample time to become attached to H 2 O or OH within the ice, forming trapped H 2 O À or OH À negative ions (anions).…”
Section: Discussionmentioning
confidence: 95%
“…Some of the photoproducts were isolated from irradiated samples by column chromatography for analytical purposes. The structures of all the products identified [chlorobenzenediols (3)(4)(5), pyrocatechol (6), hydroquinone (7), phenol (8), chlorobiphenyldiols (9)(10)(11), and dichlorobiphenyldiols (12)] are shown below. Authentic analytical standards of 3-8 were purchased, compounds 9-11 were synthesised, 23 and photosolvolysis products obtained by irradiation of liquid samples were analysed according to our previous work.…”
Section: Photoproduct Identificationmentioning
confidence: 99%
“…It is not completely transparent from 200 to 700 nm, and photoproducts identified within it include molecules of oxygen and hydrogen peroxide, atomic hydrogen, and hydroxyl radicals. [2][3][4][5][6][7][8] Radiolysis (such as γ-irradiation) of ice is known to produce relatively high concentrations of reactive species. 9- 11 The first attempts to carry out photochemical reactions in an ice matrix (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, most studies have focused on the solvation dynamics in the liquid phase, but very little is known about the initial stages of electron transfer and solvation of excess electrons in supercooled water and ice [10]. However, this knowledge is important for such diverse areas like astrophysics, environmental science, and radiation chemistry.…”
mentioning
confidence: 99%